Library information systems and e-journal archiving (Authorspress, 2005)
Contents of material: 1/ Electronic journal archiving. 2/ Access and preservation of digital archives. 3/ Archiving and preserving E-Journals. 4/ Digital preservation systems. 5/ Digitised collections. 6/ Analysing metadata creation. 7/ Digital library technology. 8/ Web-based information system. 9/ Digital books and images